A composite surface configuration towards improving cycling stability of Li-rich layered oxide materials. Issue 43 (1st November 2021) - Shi, Zhepu; Gu, Qingwen; Yun, Liang; Wei, Zhining; Hu, Di; Qiu, Bao; Chen, George Zheng; Liu, Zhaoping
Abstract : Scalable 345 W h kg −1 full pouch cells with guaranteed cycling life are achieved by employing the surface-modified materials. Abstract : Li-rich layered oxides are promising positive electrode candidates for next-generation high-energy Li-ion batteries. However, they suffer from a severe gas release issue and side reaction-induced surface degradation resulting in significant capacity fade and voltage decay. Herein, this work proposes a composite surface configuration by coordinating the three different structures from Nb/Al surface doping, surface oxygen vacancies and Al2 O3 layer via solution coating. A comprehensive characterization provided persuasive evidence that the composite surface configuration not only mitigates oxygen release but also regulates Li + ion extraction/insertion during cycling. Due to the reduced side reaction and promoted surface stability, a decent specific discharge capacity of about 270 mA h g −1 at 0.1C between 2.0 and 4.6 V vs. Li + /Li was achieved with 57.0% capacity preservation after 1000 cycles at 1C. Most importantly, a 20 A h pouch cell fabricated with this surface-modified positive electrode and an SGC/Gr-negative electrode delivered 345 W h kg −1 in specific energy and retained 77.9% of it at 0.2C after 340 cycles.